The distinctive terminology in S̆arḥ al-Kāfiya by Raḍī l-Dīn al-ʾAstarābāḏī - Sheyhatovitch, Beata (Studies in Semitic languages and linguistics, 2018)
Intro -- ‎Contents -- ‎Acknowledgements -- ‎Chapter 1. Introduction -- ‎1.1. Background -- ‎1.2. The Book's Objective -- ‎1.3. The Structure of the Book -- ‎1.4. Remarks on the Translation of Arabic Terms -- ‎Chapter 2. General Tendencies -- ‎2.1. A Tendency towards Accurate Formulations -- ‎2.2. A Tendency towards Abstract Terminology -- ‎2.2.1. Abstract Terms Derived from Grammatical Terms -- ‎2.2.2. Abstract Terms Derived from Non-technical Words -- ‎2.3. Use of "Kūfan" Terms -- ‎2.4. Terms from Other Islamic Sciences -- ‎2.4.1. Terms from Logic and Philosophy -- ‎2.4.2. Terms from Islamic Jurisprudence -- ‎Chapter 3. The Term waḍʿ and Its Derivatives -- ‎3.1. The Term waḍʿ in Grammatical Literature prior to RDA -- ‎3.2. The Term waḍʿ in Islamic Philosophy -- ‎3.3. The Term waḍʿ in Islamic Theology and Jurisprudence -- ‎3.4. The Term waḍʿ in Šarḥ al-Kāfiya -- ‎3.4.1. The Definition of waḍʿ -- ‎3.4.2. Types of Coined Elements -- ‎3.4.3. Coinage versus Usage -- ‎3.4.4. Signification by Coinage versus Other Types of Signification -- ‎Chapter 4. Terms Derived from the Roots ṭ-r-ʾ and ʿ-r-ḍ -- ‎4.1. Ṭ-r-ʾ -- ‎4.1.1. The Term ṭāriʾ in Early Juristic Works -- ‎4.1.2. Ibn Jinnī and Ibn al-ʾAnbārī's Uses of the Term ṭāriʾ -- ‎4.1.3. The Term ṭāriʾ in Šarḥ al-Kāfiya -- ‎4.2. ʿ-r-ḍ -- ‎4.2.1. The Term ʿaraḍ in Philosophy and Theology -- ‎4.2.2. Terms Derived from the Root ʿ-r-ḍ in Šarḥ al-Kāfiya -- ‎4.3. An Example of a Complex Discussion Combining Terms from Both Groups -- ‎Chapter 5. Terms Related to the Form-Meaning Relation -- ‎5.1. Maʿnā -- ‎5.1.1. Maʿnā as Abstract Meaning -- ‎5.1.2. Maʿnā as a (Non-)existent Meaning of an Element -- ‎5.1.3. Maʿnā as a Component of Meaning -- ‎5.1.4. Maʿnā as Functional Meaning -- ‎5.1.5. Maʿnā as a Meaning of Units Larger/Smaller than a Single Word -- ‎5.2. Terms Derived from the Root d-l-l